Analisis Spasial - Temporal Perubahan Tutupan Lahan di Kabupaten Maluku Barat Daya - Heinrich Rakuasa (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
Foreseeing future patterns of change and preventing or mitigating their negative impacts, it is important to understand how land cover changes. This study aims to examine changes in land cover in West Maluku Regency. To determine changes in land cover, the data used are Landsat 4-5 TM, Landsat 8 OLI, and SPOT 7 satellite images analyzed using SNI 7645:2010. The analysis includes pre-processing and land cover classification. Based on the research results, the three main MBD areas for built-up land are Moa Lakor District, Pulau Letti District, and Pulau Terselatan District. Due to Tiakur's status as the administrative center of Southwest Maluku Regency, Thakur District is the fastest-growing land development location.